2002
DOI: 10.1073/pnas.162369899
|View full text |Cite
|
Sign up to set email alerts
|

Somatic stem cells and the kinetics of mutagenesis and carcinogenesis

Abstract: There is now strong experimental evidence that epithelial stem cells arrange their sister chromatids at mitosis such that the same template DNA strands stay together through successive divisions; DNA labeled with tritiated thymidine in infancy is still present in the stem cells of adult mice even though these cells are incorporating ( . But a cell that preserves ''immortal strands'' will avoid the accumulation of replication errors only if it inhibits those pathways for DNA repair that involve potentially erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
122
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(131 citation statements)
references
References 16 publications
4
122
0
5
Order By: Relevance
“…One strategy to isolate MaSCs relies on a feature believed to be (although not universally accepted as) a key mechanism of DNA replication during stem cell division. As certain adult stem cells divide, they preferentially retain one of their DNA strands throughout multiple divisions in order to protect against the formation of deleterious mutations that occur during DNA replication [12,13]. By performing pulse-chase experiments with DNA labels, Smith et al showed there was a population of cells within the mammary gland which retained their DNA label through asymmetric segregation of DNA strands.…”
Section: Identification Of Mascsmentioning
confidence: 99%
“…One strategy to isolate MaSCs relies on a feature believed to be (although not universally accepted as) a key mechanism of DNA replication during stem cell division. As certain adult stem cells divide, they preferentially retain one of their DNA strands throughout multiple divisions in order to protect against the formation of deleterious mutations that occur during DNA replication [12,13]. By performing pulse-chase experiments with DNA labels, Smith et al showed there was a population of cells within the mammary gland which retained their DNA label through asymmetric segregation of DNA strands.…”
Section: Identification Of Mascsmentioning
confidence: 99%
“…6,7,[9][10][11][12][13] The argument usually goes in the following way. 14 If the first mutation happened in a proliferative daughter cell, it would be washed away before the second hit has a chance to confer a significant phenotypic change. On the other hand, if the first mutation occurs in the "immortal" stem cell, then its mutant progeny will populate the compartment and persist for as long as it takes to accumulate further mutations which give rise to neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…As John Cairns writes, "...there are 256 exponentially multiplying cells that divide twice a day and are being replenished continually by the divisions of a single stem cell, none of these 256 cells will ever be separated from the stem cell by more than eight divisions, and the replication errors made in those eight divisions are destined, of course, to be discarded". 14 The point of this paper is to address exactly this issue: will migrating cell mutations be indeed discarded, or is there a chance that they will persist until the second hit comes, which immortalizes the cell and thus initiates dysplasia in the crypt? In what follows we show that the intuitive argument given above is incorrect, and that despite their finite life-span, differentiated cells can stay long enough to get the first two hits.…”
Section: Introductionmentioning
confidence: 99%
“…4), the sequential nature of such a multistep process imposes a power-law behavior, that is, the age-specific incidence of cancers that arise as a consequence of several rate-limiting genomic alterations is predicted to increase with a power of age that is one less than the number of events necessary for malignant transformation. Although it is generally recognized that the carcinogenic process is more complicated and possibly punctuated by selection of advantageous mutations and clonal expansions (5), the qualitative power-law behavior of the age-specific cancer incidence is still considered a reasonable approximation for many cancers and continues to be invoked to argue for or against the importance of specific biological events in carcinogenesis (e.g., [6][7][8][9][10][11][12][13][14]. However, this assumption remains largely untested, mathematically and statistically, despite the availability of high-quality cancer data to explore its adequacy.…”
mentioning
confidence: 99%